The Evaluation of School Literacy Movement Program in Secondary School - Kristiyaningrum, Ratna Kristiyaningrum; Ismanto, Bambang (Jurnal Pendidikan dan Pengajaran, 2020)
School Literacy Movement is a program made by the government to improve the literacy skill in elementary and secondary school level. This program is the implementation of Regulation No 23 by 2015 about growing manners. This is a descriptive evaluation study that use Discrepancy evaluation model as a tool to evaluate the program. The aims of the study is to find the gaps between planning, process and result of School Literacy Movement at Secondary School that is adjusted with the vision and mission of the school and the master design of School Literacy Movement issued by Minister of Education and Culture. The stages those are observed are design, installation, process, product, and cost and benefit. The study uses interview, observe, and document study to get the data from the principal, teacher, and students. The result shows the gaps are 1) school haven’t design any training for the teacher about literacy, 2) school hasn’t prepared an instrument to evaluate the program, 3) learning stage of literacy is implemented only for Bahasa Indonesia (should be for all subjects), 4) school hasn’t prepare any cost for the literacy program. Thus, it can be concluded that there are still some gaps happened in doing the School Literacy Movement at Secondary School based on the Master Design of School Literacy Movement issued by Ministry of Education and Culture.